From PCP to MXE: a comprehensive review of the non‐medical use of dissociative drugs. Issue 7 (26th March 2014) - Morris, Hamilton; Wallach, Jason; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> PCP or phencyclidine was discovered in 1956 and soon became a popular street drug. Dissociatives including PCP, ketamine, and dextromethorphan have been used non‐medically for their mind‐altering effects for over 60 years. Many of these compounds have also been used clinically and in legitimate research. At least 14 derivatives of PCP were sold for non‐medical and illict use from the late 1960s until the 1990s. With the advent of the Internet, the drug market underwent a dramatic evolution. While initially gray‐market chemical vendors offering dextromethorphan and ketamine thrived, most recently the market has shifted to legal high and online‐based research chemical vendors. Starting with the first dissociative research chemical, 4‐MeO‐PCP in 2008, the dissociative research chemical market has rapidly evolved and currently comprises at least 12 dissociatives, almost half of which were unknown in the scientific literature prior to their introduction. Several of these, including methoxetamine, have reached widespread use internationally. A historical account of non‐medical use of over 30 dissociative compounds was compiled from a diverse collection of sources. The first complete portrait of this underground market is presented along with the relevant legal, technological, and scientific developments which have driven its evolution. Copyright © 2014 John Wiley & Sons, Ltd.